Prenatal Diagnosis of Tay-Sachs Genotypes - Navon, Ruth (1971)
Hexosaminidase activity was determined in cultured and uncultured amniotic fluid cells taken from seven pregnant women who had previously given birth to infants with Tay-Sachs disease. Complete deficiency of hexosaminidase A was found in one case, indicating a Tay-Sachs fetus. The diagnosis was confirmed on examination of various tissues after therapeutic abortion. Of the other six cases three were considered heterozygous and three homozygous normal. These diagnoses were confirmed postnatally on examination of cord blood leucocytes, peripheral leucocytes, and urine. The activity of hexosaminidase A is appreciably decreased in dead cells and hence in uncultured amniotic fluid cells. Hence reliable identification in utero of the three genotypes may be achieved only by examining the cultured living amniotic cells.